Cohort Models of Learning: Adapting Content to Women’s Learning Styles - Fedor, Janice (Journal of Leadership, Accountability and Ethics, 2017)
Do educational cohorts help or hurt learning? While economically desirable as an educational delivery model, a debate exists as to whether cohorts improve the learning process or diminish the learning outcomes (Pemberton & Akkary, 2010). This qualitative research examined sixteen non-traditional aged female college students who were enrolled in an intensive 20-month bachelor’s degree completion program. The most dramatic influence of spending time in a cohort was the progression from one epistemological category to the next, which had the most profound influence on the women inside the program and in their personal lives (Belenky, Clinchy, Goldberger, & Tarule, 1997).